ANALISIS HUKUM ISLÂM TERHADAP MASALAH KEKERASAN DALAM RUMAH TANGGA (KDRT) - Abd. Wahed (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2009)
KDRT (domestic violence) must be ended. Both wife andhusband come to a conclusion to finish it. However, itdoesn't mean that the role of a husband, as disciplineupholder, has to be denied. Islam does not agree with it.As an Imam (leader), a husband must maintain moralvalues to establish a peaceful and perfect harmoniousfamily. UU. No 23 Th. 2004 implicitly states that domesticviolence is any violence types occurring in a family. Ahusband has been a person who always be blamed on inthis case. This article analyzes a kind of violencecommitted by a husband against the family members—children and wife from the perspective of Fiqh (Islamiclaw)